"But the moment they find out that you are MSM...": a qualitative investigation of HIV prevention experiences among men who have sex with men (MSM) in Ghana's health care system - Sameer Kushwaha; Yasmin Lalani; Geoffrey Maina; Adedotun Ogunbajo; Leo Wilton; Thomas Agyarko-Poku; Yaw Adu-Sarkodie; Francis Boakye; Nanhua Zhang; LaRon E. Nelson (BMC, 2017)
Abstract Background The prevalence of HIV in Ghana is 1.3%, compared to 17% among men who have sex with men (MSM). There is limited empirical data on the current health care climate and its impact on HIV prevention services for Ghanaian MSM. The purposes of this study were to investigate (1) MSM's experiences using HIV prevention resources, (2) what factors, including health care climate factors, influenced MSM's use of prevention resources and (3) MSM self-identified strategies for improving HIV/sexually transmitted infection (STI) prevention among MSM in Ghanaian communities. Methods We conducted 22 focus groups (n = 137) with peer social networks of MSM drawn from three geographic communities in Ghana (Accra, Kumasi, Manya Krobo). The data were examined using qualitative content analysis. Interviews with individual health care providers were also conducted to supplement the analysis of focus group findings to provide more nuanced illuminations of the experiences reported by MSM. Results There were four major findings related to MSM experiences using HIV prevention resources: (1) condom quality is low, condom access is poor, and condom use is disruptive, (2) inaccurate information undermines HIV testing (3), stigma undermines HIV testing, and (4) positive attitudes towards HIV prevention exist among MSM. The main healthcare climate factors that affected prevention were that MSM were not free to be themselves, MSM were not understood by healthcare providers, and that MSM did not feel that healthcare providers cared about them. To improve HIV prevention MSM suggested increased education tailored to MSM should be provided to enable self-advocacy and that education and awareness are needed to protect human rights of MSM in Ghana. Conclusion MSM in Ghana are exposed to negative health care climates. Health care spaces that are unsupportive of MSM's autonomy undermine the uptake of prevention measures such as condoms, HIV testing, and accurate sexual health education. These findings contribute to knowledge to inform development of HIV prevention interventions for MSM in Ghana, such as culturally appropriate sexual health education, and digital technology to connect individuals with resources supportive of MSM.